Effects of first aid training in emergency preparedness and response - Pawłowski, Witold; Lasota, Dorota; Goniewicz, Krzysztof; Goniewicz, Mariusz (Medical Studies/Studia Medyczne, 2018)
The study deals with the relation between the level of public awareness in maintaining safety, responsibility for others and First Aid skills and accident rate and mortality rates in the event of emergency. The available data show that when immediate assistance is provided within 5 minutes after the accident, the wounded survival rate is 85%, while over 15 min it is 72%, and 20 min from the event it is 60%. What is most important and probably yields the most impact is the reform of education, which provides training in First Aid at all levels of education and has the task of shaping a new, conscious society. For that reason the role of schools is very important, as it influences development and prepares students to meet the various challenges of the modern world, including assistance to victims, the emergency response, and care for their own safety, victims and witnesses.